Carbon Capture Project Smallholder (as) and Medium (as) Producers ( as) of the Brunca Region , Costa Rica - Navarrete, Gilmar (2013)
The Clean Development Mechanism (CDM) of the Kyoto Protocol, allows the non  Annex 1 countries to receive projects that contribute to reducing greenhouse gas emissions and sustainable development in developing countries. The CDM, since its inception, has issued credits equivalent to 1.434.737.562 tons of CO2, distributed across 7.450 projects around the world, from 15 different sectors. Sectors 14 that allow forestry projects (such as reforestation and afforestation) have registered 53 projects to date; 19 of which are in Latin America.  Nevertheless, the contribution of this sector currently represents less than 1% of CDM Certificates of Emissions Reduction (CERs) issued. In September 2013, through their National Forestry Financing Fund (FONAFIFO), Costa Rica registered their first CDM project with the United Nations Framework Convention on Climate Change (UNFCCC), after having complied with all the project cycle processes. The project, known as "Carbon Sequestration in Small and Medium Farms, Brunca Region, Costa Rica" was a project executed by FONAFIFO under their Environmental Services Payment Program. This project was developed in Pérez Zeledón, San José, Costa Rica in partnership with the Cooperative Corporation CoopeAgri RL. The total goal of the project is to reduce the greenhouse gas emission by 176,050 ton of CO2-e, in a period of 20 years and commercialize the CERs  in the regulated carbon market.